2021
DOI: 10.3390/healthcare9040436
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Evidence of Impacts of COVID-19 Outbreak on Sexual and Reproductive Health: A Scoping Review

Abstract: Introduction: The emergence of the coronavirus disease 2019 (COVID-19) pandemic has rapidly transformed the pre-existing worldwide sexual and reproductive health environment. The provision and supply of contraceptives, and a wide variety of sexual health, new-born, and maternal health services have been seriously affected. Thus, this scoping review mapped the available evidence on the impacts of the COVID-19 outbreak on sexual and reproductive health. Methods: Arksey and O’Malley’s methodological framework gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…65 Similarly, although not directly comparable as most studies in the reviews came from high-income settings, two reviews showed adverse effects of COVID-19 on hospital visits, hospitalisations, diagnostics, and maternal and child health services. 19 66 Furthermore, the current study showed that the pandemic had also affected the mental health status of healthcare workers due to fear of infection and work-related stress. The findings from Africa were consistent with those from Thailand, which revealed that the COVID-19 pandemic led to uncertainty, anxiety, fear and stigmatisation among healthcare workers.…”
Section: Discussionmentioning
confidence: 69%
“…65 Similarly, although not directly comparable as most studies in the reviews came from high-income settings, two reviews showed adverse effects of COVID-19 on hospital visits, hospitalisations, diagnostics, and maternal and child health services. 19 66 Furthermore, the current study showed that the pandemic had also affected the mental health status of healthcare workers due to fear of infection and work-related stress. The findings from Africa were consistent with those from Thailand, which revealed that the COVID-19 pandemic led to uncertainty, anxiety, fear and stigmatisation among healthcare workers.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, the impact of the pandemic on contraceptive use depends on several factors such as the methods used by couples, types of disruptions experienced, and their need for contraceptives at a particular point in time (11). However, the literature has almost exclusively focused on the impact of COVID-19 on the use of pre-coital contraceptive methods, with limited attention given to the impact of COVID-19 on the use of post-coital contraceptives (2,(10)(11)(12)(13). Hence, there is limited empirical evidence on the impact of infectious disease outbreaks on the use of emergency contraceptives (ECs) in a pandemic situation.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that our results are applicable to the Czech setting and patients using outpatient diabetes services, even during the COVID-19 pandemic. However, we are aware that in some other segments of health care or in other regions [ 50 , 52 , 53 ] the impact of this pandemic may have a non-negligible effect, not only on the spatial patterns of health service use.…”
Section: Discussionmentioning
confidence: 99%